Female Genital Mutilation in Infants and Young Girls: Report of Sixty Cases Observed at the General Hospital of Abobo (Abidjan, Cote D'Ivoire, West Africa) - Kouie Plo; Kouadio Asse; Dohagneron Seï; John Yenan (Hindawi Limited, 2014)
The practice of female genital mutilations continues to be recurrent in African communities despite the campaigns, fights, and laws to ban it. A survey was carried out in infants and young girls at the General Hospital of Abobo in Cote D'Ivoire. The purpose of the study was to describe the epidemiological aspects and clinical findings related to FGM in young patients. Four hundred nine (409) females aged from 1 to 12 years and their mothers entered the study after their consent. The results were that 60/409 patients (15%) were cut. The majority of the young females came from Muslim families (97%); the earlier age at FGM procedure in patients is less than 5 years: 87%. Amongst 409 mothers, 250 women underwent FGM which had other daughters cut. Women were mainly involved in the FGM and their motivations were virginity, chastity, body cleanliness, and fear of clitoris similar to penis. Only WHO types I and II were met. If there were no incidental events occurred at the time of the procedure, the obstetrical future of these young females would be compromised. With FGM being a harmful practice, health professionals and NGOs must unite their efforts in people education to abandon the procedure.